Cognitive Behavioral Therapy In Building Visionary Leaders - Baso, Rachmie Sari; Alwy, Muhammad Adenuddin; Wijadjanti, Suzana (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze how cognitive behavioural therapy builds visionary leaders so that they can increase the efficacy of the performance of leaders in educational institutions, which refers to the phenomenon of many leaders who lead but tend to have a concept of monotonous thinking without any foresight in improving the quality of the institutions they lead. This study uses a qualitative approach with a type of phenomenology, where researchers use interviews, observation and documentation to obtain data as a medium to describe the meaning and phenomena that occur in the field. The study results show that cognitive behavioural therapy in building visionary leaders is obtained from; role models, environmental culture, building positive habits, and visionary leader commitment. The implications obtained from cognitive behavioural therapy can build the visionary thinking of leaders to improve the quality of their leadership further.